Reducing divorce rates: the role of the communicative religious leader in Aceh - Halihasimi; M.S., Anwar; Rizki, Fauza (Jurnal Studi Komunikasi, 2024)
This study examines the function of da’wah communication in disseminating knowledge, education, and counsel to mitigate divorce rates in Central Aceh Regency. This study incorporated A descriptive qualitative methodology, specifically observation, interviews, and document analysis of pertinent literature, legislation, regulations, and scholarly publications . This methodology provided comprehensive insights into the intricate dynamics of da’wah communication and its influence on marital stability. The study investigated three principal questions: What impact does da’wah communication as an information provider have on divorce rates? How does its educational role affect marital stability? How does its advisory role aid in decreasing divorce rates in the Central Aceh District? The results demonstrate that da’wah communication significantly lowers the divorce rate in Central Aceh District by functioning as a source of knowledge, education, and guidance; effectively resolving family disagreements is essential for fostering patience and encouraging spouses to uphold marital integrity under divine guidance. In contrast, families who do not engage in da’wah communication are more susceptible to issues, misunderstanding, and divorce. These findings underscore the need to incorporate da’wah communication into community initiatives to mitigate divorce rates and promote healthier family relations. Future studies may investigate the enduring impacts of da’wah communication on marital stability and its possible implementation in many cultural settings.